In Praise of Development Economics (Distinguishedl Lecture) (The Pakistan Development Review, 1989)
In some branches of the subject notably development economics ... , the neglect of reality has compounded the profusion of crude lapses to bring.about a situation so unsatisfactory that [this] branch of economics may have retrogressed rather than progressed in recent decades. For instance, books published a generation or two ago, such as those by Vera Anstey, Allan McPhee and W. K. Hancock, are more informative and of greater predictive usefulness than much of the more recent development literature. This literature is often less informative and less useful as a guide to policy than many of the publications of artthropologists, economic historians or observers such as Nirad Chaudhuri, Noni Jabavu and V. S. Naipaul who actually know the societies they write about. Indeed over a wider area, the fiction of Joseph Conrad, Rudyard Kipling, R. K. Narayan, R. Prawer Jhabvala, and So1.zhenitsyn is more informative on many aspects and relations of economic life than the publications of many economists in major branches of the subject. Their fiction is rooted in reality